Antiandrogênios em efluente hospitalar: extração com barras poliméricas, quantificação, identificação de metabólitos e subprodutos, proposição de rotas de degradação por processos avançados de oxidação - Brenner, Carla Geane Brandenburg (2013)
In this work, methods were developed for the determination of antiandrogens in hospital effluent using the analytical technique HPLC-DAD. Microextraction techniques of Spironolactone, Flutamide, Cyproterone and Tamoxifen were investigated: liquid-liquid (LLME) and sorptive extraction (SBSE). For quantification of the analytes in hospital effluent was used solid phase extraction (SPE) with recoveries of 75.0 to 109.0±1.0 to 13.0% in aqueous solution and from 72.0 to 106.0±2.0 to 13.0% in hospital effluent. The average concentrations of analytes in the effluent of emergency (PA) ranged from 0.00 to 11.70 μg L-1 (RSD 0.00 to 11.5%) and of general-HUSM 0.00 to 11.30 μg L-1 (0.00 to 6.78% RSD), respectively. LC-ESI-MS/MS technique was used for fragmentation of the precursor ions, to identify product ions, and for neutral mass loss. LC-ESI-QqLIT-MS/MS was used to identify metabolites and subproducts. STR photoreactor of 800 mL was used for simple photolysis and heterogeneous photocatalysis, and for ozonation, column reactor of 800 mL. Fractional factorial design was applied to the extraction experiments, as well as, to AOPs. UV-radiation was generated by mercury vapor lamp of 125 W and 401 W m-2. Polymer bars of polydimethylsiloxane and polyurethane with TiO2 supported were developed for photocatalysis. Kinetic studies of the degradation reactions were made, subproducts were identified and fragmentation routes proposed. Metabolites were identified in hospital effluent. Preliminary risk analysis revealed that spironolactone has lower environmental risk, and that all analytes except tamoxifen, show PEC value > 0.01 μg L-1.